Late-onset neurological symptoms in thalidomide-exposed subjects: a study of an Australasian cohort - Jankelowitz, S. K.; Spies, J. M.; Burke, D. (European journal of neurology, 2013)
Background and purpose Thalidomide was marketed for the treatment of morning sickness and resulted in foetal death and physical deformities. The exact mechanism of action of thalidomide in its teratogenicity is still actively debated in the literature. Methods This study reviewed 16 of the confirmed Australasian victims of in utero exposure to thalidomide who now presented with new‐onset neurological symptoms in the fourth and fifth decades. Results Clinical neurological examination and neurophysiological investigations revealed that new symptoms were due in part to compressive neuropathies, often exacerbated by the adaptations made to accommodate the disability and poor mobility arising from the limb deformities. Other subjects were found to have musculoskeletal symptoms due to compensatory postures employed to perform tasks of daily living. Conclusions The study provides no evidence of ongoing loss of neurons or late reactivated neural degeneration and no evidence of a generalized peripheral neuropathy. Rather, the development of new symptoms in subjects can be explained by compressive neuropathies and compensatory postures employed to perform tasks of daily living.